NECESSITY AND PROBLEMS OF TAKING INTO ACCOUNT NON-PRICE CRITERIA IN PUBLIC PROCUREMENT IN UKRAINE (Economic journal of Lesya Ukrainka Volyn National University, 2021)
Annotations.Introduction. The of the electronic system of purchases Prozorro allowed substantially to promote efficiency of public purchases on all levels, though did not decide all problems. One of problems is that customers are oriented on a supply price at the choice of supplier and does not take into account the cost of life cycle. It negatively influences on the cost of the use of commodity and its utilization in the future. In addition, the Ukrainian customers rarely take into account the tendency of increase of part of "green" purchases in the countries of European Union, it can negatively affect structure of our export to the countries EU, where in the nearest years the so-called carbon track will undertake to attention at the commodities imported in EU.Rezults. Foreign and Ukrainian experts mark the necessity of the use of not only price criterion during realization of tenders but also all spectrum of criteria for the estimation of tender suggestions. In Ukraine a price is a qualificatory criterion for the choice of supplier of commodity(services) from the point of view of budgetary cost effectiveness, but the use of non-price criteria for the estimation of tender suggestions did not yet become widespread practice in Ukraine. At the same time, it can negatively affect actual implementation of obligations under contracts for the supply of goods, works and services, especially in the context of overcoming the consequences of the economic crisis of 2020. Conlusions. In order to implement the Association Agreement with the European Union, when conducting tender procurement in Ukraine, special attention should be paid to such a new criterion as the share of "green" energy that will be used in the production of a product. For implementation of Agreement about an association with European Union the special attention it follows to spare to such criterion as part of "green" energy that will be used for the production of that or other commodity during realization of tender purchases in Ukraine. The EU will pay increasing attention to this factor when assessing the environmental friendliness of goods imported into the European Union through evaluation.